2018
DOI: 10.18632/oncotarget.26077
|View full text |Cite|
|
Sign up to set email alerts
|

N-(2′-Hydroxyphenyl)-2-propylpentanamide (OH-VPA), a histone deacetylase inhibitor, induces the release of nuclear HMGB1 and modifies ROS levels in HeLa cells

Abstract: N-(2′-Hydroxyphenyl)-2-propylpentanamide (OH-VPA) is a valproic acid (VPA) derivative with improved antiproliferative activity toward breast cancer (MCF-7, MDA-MB-231, and SKBr3) and human cervical cancer cell lines (HeLa) compared to that of VPA. However, the pharmacological mechanism of OH-VPA activity remains unknown. High-mobility group box 1 (HMGB1) is an important enzyme that is highly expressed in tumor cells and has a subcellular localization that is dependent on its acetylation or oxidative state. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In addition, HMGB1 was translocated from the nucleus to the cytoplasm in the cells treated with HO-AAVPA, suggesting that HMGB1 is acetylated and it cannot back to the nucleus, therefore, acetylated HMGB1 could exit from the cell and participate in cell death [ 13 , 15 ]. In addition, an increase of HMGB1 in the cytoplasm is in agreement with the amount of O 2 −· produced at each concentration, as was demonstrated in HeLa cells in which after HO-AAVPA treatment induced oxidative stress and also the levels of acetylated HMGB1 were increased, and these results were also linked with the possible HDAC1 inhibition [ 26 , 31 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, HMGB1 was translocated from the nucleus to the cytoplasm in the cells treated with HO-AAVPA, suggesting that HMGB1 is acetylated and it cannot back to the nucleus, therefore, acetylated HMGB1 could exit from the cell and participate in cell death [ 13 , 15 ]. In addition, an increase of HMGB1 in the cytoplasm is in agreement with the amount of O 2 −· produced at each concentration, as was demonstrated in HeLa cells in which after HO-AAVPA treatment induced oxidative stress and also the levels of acetylated HMGB1 were increased, and these results were also linked with the possible HDAC1 inhibition [ 26 , 31 ].…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, these results correlated with docking results showing that HO-AAVPA is capable to be accommodate at catalytic site of HDAC1 enzyme, suggesting that it affects the deacetylation activity. Thus, it explains the increase acetylation of HMGB1 due to HDAC1 inhibition, then, the HO-AAVPA favored the acetylate HMGB1 [26,[31][32][33][34]. All these processes, such as HDAC1 inhibition as well HMGB1 acetylation, could be related with the cytotoxic effect observed for HO-AAVPA (IC50 = 1.6 mM at 48 h).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Analysis of cysteine through the predictive metabolic results allows us to reinforce the importance of this amino acid in the effect of VPA due to its participation in several metabolic pathways such as coenzyme biosynthesis, cysteine biosynthesis and degradation, hydrogen sulfide biosynthesis and homocysteine degradation, serotonin, and taurine biosynthesis, and others. Cell redox capacity is another worth mentioning subject, Contis-Montes de Oca et al (2018) found that HO-VPA, a novel compound partly based on VPA which shares many of its effects, increased ROS levels (through HMB1 acetylation) and decreased cell viability in HeLa cells [ 32 , 33 ]. Reduction in cysteine availability, a known limiting factor in GSH synthesis, may play a key role in cell death through glutathione shortage [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Saito et al, 1999;Lauffer et al, 2013;Gorshkov et al, 2019) HDAC1 19) presented an activity against HeLa cells and IC 50 value of 0.92 mM and increased intracellular levels of ROS after treatment with a concentration of 0.8 mM. (Oca et al, 2018;Sixto-López et al, 2020) HDAC1:153.78 µM HDAC6:>1000 µM HDAC8:>1000 µM Luotonin A derivative (20) Inhibition of HDAC 1 and 2 Compound (20) presented an antiproliferative activity against HeLa cells identical to Luotonin A, its precursor; however, the selective index was 4.4 times superior for the synthesized compound compared to Luotonin A. Compound (20) treatment also resulted in induction of p53 protein and G1 arresting cell cycle.…”
Section: -Aminobenzamide Derivativesmentioning
confidence: 99%